The Land Is Ours: Bottom-Up Strategies to Secure Rural Women's Access, Control and Rights to Land in Kenya, Mozambique, Senegal and Malawi - Santpoort, Romy; Steel, Griet; Mkandawire, Andrew; Ntauazi, Clemente; Faye, El Hadji; Githuku, Fridah (Frontiers in Sustainable Food Systems, 2021)
Despite their key role in agriculture, in many African regions, women do not have equal access to or control and ownership over land and natural resources as men. As a consequence, international organizations, national governments and non-governmental organizations have joined forces to develop progressive policies and legal frameworks to secure equal land rights for women and men at individual and collective levels in customary tenure systems. However, women and men at the local level may not be aware of women’s rights to land, and social and cultural relations may prevent women from claiming their rights. In this context, there are many initiatives and programs that aim to empower women in securing their rights. Still, little is known about the existing strategies and practices women employ to secure their equal rights and control over land and other natural resources. In particular, the experiences of women themselves are somewhat overlooked in current debates about women’s land rights. Therefore, the foundation of this paper lies in research and action at the local level. It builds on empirical material collected with community members, through an action research program in Kenya, Senegal, Malawi and Mozambique. This paper takes the local level as its starting point of analysis to explore how the activities of women (among others) and grassroots organizations contribute to increased knowledge and concrete actions to secure women’s land rights in customary tenure systems in sub-Saharan Africa. It shows three important categories of activities in the vernacularization process of women’s land rights: (1) translating women’s land rights from and to local contexts, (2) realizing women’s land rights on the ground, and (3) participatory monitoring of progresses of securing women’s land rights. With concrete activities in these domains, we show that, in collaboration with grassroots organizations (ranging from grassroots movements to civil society organizations and international federations), rural women managed to strengthen their case, to advocate for their priorities and preferences during land-use planning, and demand accountability in resource sharing. In addition, we show the mediating role organizations working on the ground play in providing women with secure rights to land and other natural resources.